PERLINDUNGAN KONSUMEN DALAM MEMBERIKAN REVIEW PRODUK YANG JUJUR DI MEDIA SOSIAL - Vanessa Stefanie; Shafira Andiena; Lau FannyLian (PROSIDING SERINA, 2021)
This article discusses consumer protection of people whoreview honestly on social media about cosmetic products that are sold freely in the market. We can access a lot of information about anything, one of which is information about cosmetic products. However, in the end he was entangled in a case. In fact, there are still many people and business people who do not accept if their products are judged honestly but have a negative effect on society. They consider it a threat not an appeal to improve the quality of the product. People who spread negative reviews are asked to apologize to the product because it is considered defamatory. So, people are increasingly distrustful, whether this product is really good as it is. In fact, consumers do not know clearly how to express opinions properly and correctly on social media so that they can be entangled in criminal acts if business actors want to take this matter to the legal realm. So, it is necessary to solve the problem from both parties first. Disseminating information to social media can be done if it has the aim of giving an appeal to the public without referring to anyone.Artikel ini membahas mengenai perlindungan konsumen terhadap orang yang me-review secara jujur dimedia sosial mengenai produk kosmetik yang dijual bebas dipasaran. dapat mengakses banyak informasi mengenai apa saja, salah satunya informasi mengenai produk kosmetik. Pada kenyataannya, masih banyak orang maupun pelaku usaha yang tidak terima jika produk mereka dinilai dengan jujur namun berefek negatif bagi masyarakat. Mereka menganggap itu sebagai ancaman bukan himbauan untuk memperbaiki kualitas produk. Orang yang menyebarkan review negatif diminta untuk meminta maaf kepada produk tersebut karna dianggap mencemarkan nama baik. Sehingga, orang semakin tidak percaya, apakah produk ini benar bagus apa adanya. Nyatanya konsumen tidak mengetahui secara jelas bagaimana cara mengemukakan pendapat dengan baik dan benar di media sosial sehingga mereka dapat terjerat tindak pidana jika pelaku usaha ingin melanjutkan masalah ini ke ranah hukum. Sehingga, perlu adanya penyelesaian masalah dari kedua belah pihak terlebih dahulu. Menyebarkan informasi ke media sosial dapat dilakukan jika memiliki tujuan untuk memberi himbauan kepada masyarakat tanpa merujuk kepada siapapun.